Ecosystem-based Adaptation Planning in the Panchase Mountain Ecological Region - Park, Jaeyoon; Alam, Mozaharul (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
As part of numerous efforts on adapting to climate change in Nepal, an approach of Ecosystem-based Adaptation (EbA) is being demonstrated in the Panchase Mountain Ecological Region (PMER). Partners under the project entitled Ecosystem-based Adaptation in Mountain Ecosystems in Nepal have been implementing activities to reduce vulnerability of the PMER to climate change and enhance resilient capacity of communities and ecosystems in the region to cope with adverse impacts of climate change already being witnessed. This article places focus on the process of EbA planning and preliminary lessons learned through the project activities in particular at local and ecological level. Reflection and suggestion on EbA planning presented in the article is expected to help all stakeholders in the Himalayan region and beyond design and implement future climate change adaptation activities to be more effective and efficient while empowering local communities and ensuring social, economic and environmental sustainability. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015